Weed menace and management strategies for enhancing oilseed brassicas production in the Indian sub-continent: A review. (June 2017) - Shekhawat, Kapila; Rathore, Sanjay Singh; Dass, Anchal; Das, Tapas Kumar; Mahajan, Gulshan; Chauhan, Bhagirath Singh
Abstract: Oilseed brassicas (OSB) contribute 28.6% to the total oilseed production in India, sharing 27.8% in its oilseed economy. Despite phenomenal increases in production after the launch of Technology Mission on Oilseeds, a gap of 9 million tonnes (MT) edible oils remains between current production (8 MT) and demand (17 MT). This gap could be abridged by enhancing existing OSB productivity from 1.25 t ha −1 to at least world's average (1.97 t ha −1 ). Among the various biotic stresses that OSB experience, weeds including Aesphodelus tenuifolius, Anagallis spp., Chenopodium spp., Argemone mexicana, and Orobanche aegyptica, cause yield reductions from 30% to complete crop failure. Weeds pose serious concerns for the ecosystem stability and socio-economic development of small and marginal farms, particularly in semi-arid regions. Conventional manual weeding has become impractical due to labour shortages and escalating costs. Commonly used dinitroaniline herbicides could improve economic returns, but they are not effective against a wide spectrum of weeds. Multi-tactic approaches, integrating tillage, improved crop husbandry, host-plant resistance, breeding herbicide-tolerant cultivars, innovations in farm implements, and use of broad-spectrum herbicides are vital to overpass the existing 78% technological gap for weed control in OSB producing areas of India. Integrating these different weed control methods may enhance mustard yield by 20–200%, besides improving quality and environmental sustainability. This review summarizes the advances made so far in weed management strategies, and identifies new areas of research that can make an important contribution towards realizing the production goal of 24 MT oilseeds in India by 2020 AD. Highlights: Weeds cause huge yield losses (35–65%) in oilseed brassicas (OSB). Changing weed flora under conservation agriculture requires the use of diverse herbicide combinations. Exploration of self-supportive allelopathy and introduction of herbicide–tolerant OSB can overcome weed problems. Integrated weed management offers viable solution to the problem of divergent weed flora in OSB.